Design and testing of slide vibrational compaction device - Lang, Chunling; Qian, Haifeng; Zhu, Zirui; Wei, Yanpeng; Wang, Han; Zhao, Jiale; Gong, Jianguang (International Journal of Agricultural and Biological Engineering, 2025)
In light of the shortcomings in soil compaction observed in ridge cultivation following seeding in Northeast China, it was deemed necessary to develop a solution that would address the issue of soil moisture conservation and temperature control on the seedbed. The slide vibrational compaction device (SVPD), which is capable of compacting the upper and lateral soil of the ridge, was thus designed. The device features adjustable parameters, including an upper compacting plate inlet width of 260-360 mm, an outlet width of 230-290 mm, and a side compacting plate width of 140-240 mm. Its key components include an eccentric block generating vibratory force, a spring system with adjustable stiffness for controlled compaction, and compacting plates designed for uniform soil coverage. The optimal working parameters were determined to be an eccentric block angle of 36.00°, spring stiffness of 46.00 N/mm, and an upper plate exit width of 284.00 mm. The device achieves soil bulk densities of 1.206 g/cm3 on the ridge and 1.148 g/cm3 on the ridge side, significantly improving compaction compared to traditional methods, and increasing maize yield by 5%. Therefore, in order to meet the agronomic requirements of soil bulk density for crop growth on the ridge, the sliding vibration compacting device also achieves effective compaction of the soil on the ridge side, providing effective technical support for crop emergence and growth under the monoculture planting pattern in Northeastern China.Keywords: sliding, vibratory ballast, design and testing, soil bulk densityDOI: 10.25165/j.ijabe.20251803.9140Citation: Lang C L, Qian H F, Zhu Z R, Wei Y P, Wang H, Zhao J L, et al. Design and testing of slide vibrational compaction device. Int J Agric & Biol Eng, 2025; 18(3): 105–115.